Implementation of lead niobate zirconate titanate (PNZT) thin films as passive monolithic microwave integrated circuit elements / Suhana Sulaiman - Sulaiman, Suhana (Institute of Graduate Studies, UiTM, 2013)
Lead zirconate titanate (PZT) and lead niobate zirconate titanate (PNZT) belong to the ferroelectric family. They have high dielectric constants whereby the use of these materials allows reduction of circuit size. This research is focused on microwave characterization of films made of these materials for monolithic microwave integrated circuit (MMIC) applications. Both films are deposited on silicon substrates using different deposition techniques. PZT films are deposited with sputtering to give thickness of 0.5 mm. The films have morphotrobic boundary phase since their Zr/Ti ratio is 50/50. In contrast, PNZT films are grown using metal organic deposition to give thickness of 1 mm. PNZT films are doped with 4 % of niobium (Nb) with a Zr/Ti ratio of 20/80. Capacitors and transmission lines made of PZT and PNZT were fabricated using standard semiconductor processing. High frequency wafer probes were used to carry out microwave measurement from 5 to 20 GHz, and from this the results were used to correlate microstructure properties to high frequency behavior. X-ray diffraction and scanning electron microscopy were employed to investigate grain texture and crystalline properties. The X-ray diffraction results show that PNZT has higher peak of intensity as compared to PZT…